NEBUCHADNEZZAR II AND ARCHAEOLOGICAL SUBSTANTIATION OF NEO-BABYLONIAN EMPIRE - Gosal, Fellix (Klabat Theological Review; Vol 4 No 1 (2024): Klabat Theological ReviewDO - 10.31154/ktr.v4i1.1070.1-12, 2024)
The ancient Neo-Babylonian Empire has made significant contributions to the field of archaeology, particularly within the Mesopotamian region. The zenith of this kingdom’s prosperity is notably chronicled in the Book of Daniel within the Old Testament. In Daniel 4:30, King Nebuchadnezzar arrogantly acknowledges himself as the architect behind the magnificent city. While certain assertions suggest that the initiation of this construction project may have commenced under his predecessor, King Nabopolassar, a comprehensive examination of the Aramaic term “bena” is indispensable for a nuanced comprehension of the biblical narrative. Keyword: Neo-Babylonian Empire, Nebuchadnezzar, Biblical Archaeology.